PENGARUH KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2017-2021 - Etnandia Tri Wulandari; Evaliati Amaniyah (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study is to determine the financial performance of financial distress in food and beverage subsector companies listed on the Indonesian stock exchange for the 2017-2021 period. The selected p opulation was the food and beverage subsector of 32 companies, the sample was selected using the purpose sampling method as many as 22 companies that were sampled in the study. The variables used in this study are liquidity ratio, profitability ratio, leverage ratio, and activity ratio as independent variables, financial distress as dependent variables. The data analysis technique used in this study is multiple linear regression analysis, with hypothesis testing of t statistical tests and f statistical tests with SPSS (statistical product and service solutions) application tools. The results of this study prove that: (1) The ratio of likuidity has a positive and significant effect on financial distress (2) The ratio of profitability has a positive and significant effect on financial distress (3) The leverage ratio has a negative and significant effect on financial distress (4) Ratio Activity has a positive and significant effect on financial distress.